Evaluation of Factors that Predict the Success Rate of Trial of Labor after the Caesarian Section among Women with One Previous Scar at St. Francis Referral Hospital Ifakara, Tanzania - Sylivester W. Mkama (Achievements and Challenges of Medicine and Medical Science Vol. 4, 2024)
Background: A trial of labor is a safe option for most women after one previous caesarean delivery. The specific objective of the study was to determine the rate of VBAC among women with one previous scar at St. Francis Referral Hospital, Ifakara, Tanzania, to determine obstetric factors influencing the success of VBAC among women with one previous scar. Methods: This descriptive cross-sectional study was conducted from January 01 to December 31, 2023. A total of 133 pregnant women with one previous scar were enrolled. Interviews were conducted with all participants. Results: The analysis includes 133 pregnant women with one previous scar attending the outpatient department obstetric clinic. Of these 37.6% were aged between 21-29 years; 52.6% were Christian, 90.2% were married, 45.1% were secondary, 45.1% were self-employed, and 37.6% were parity 1. Regarding gestation (weeks), 62.4% were 37-42 weeks, and 67.7% attended ANC. Among them, 63.9% were 2 ANC visits. Emergency caesarean delivery; accounts for 82.7% while 75.2% underwent pfannestiel incision. The Operation Duration was 30-60 min for 48.9% with 75.2% experiencing Intraoperative blood loss of; 500-1000mls. Antibiotic administration was post-operative in; 81.7%, and 18.8% had previous uterine incision extension. Conclusion: This study shows that pregnant women with one previous scar attending an outpatient department obstetric clinic can successfully undergo VBAC. Promoting VBAC by emphasizing favorable during counseling enhances its prevalence.